2018
DOI: 10.1093/gji/ggy406
|View full text |Cite
|
Sign up to set email alerts
|

P-wave dispersion and attenuation due to scattering by aligned fluid saturated fractures with finite thickness: theory and experiment

Abstract: Fractures often play an important role in controlling the fluid flow in hydrocarbon reservoirs. When the seismic wave propagates through media containing fracture corridors, significant scattering dispersion and attenuation can occur. In this work, we study the P-wave dispersion and attenuation due to the scattering caused by 2-D fluid-saturated aligned fractures with finite thickness, which are embedded in an isotropic elastic background medium. Using the Foldy approximation and the representation theorem, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…Hence, we can first calculate θ ( ξ ) through equation . It is not easy to solve equation analytically, but it can be solved numerically (e.g., Guo, Shuai, et al, ). In order to do so, we need to discretize equation as follows: j=0N1{}M(),ziξjnormalΔξ+δijθ()ξj=p0zi,i=0,1,,N1, where N is the number of discretized points, Δξ = a / N , z i = iΔξ , ξ j = jΔξ , and δ ij is the Kronecker's delta.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, we can first calculate θ ( ξ ) through equation . It is not easy to solve equation analytically, but it can be solved numerically (e.g., Guo, Shuai, et al, ). In order to do so, we need to discretize equation as follows: j=0N1{}M(),ziξjnormalΔξ+δijθ()ξj=p0zi,i=0,1,,N1, where N is the number of discretized points, Δξ = a / N , z i = iΔξ , ξ j = jΔξ , and δ ij is the Kronecker's delta.…”
Section: Theorymentioning
confidence: 99%
“…However, we can note that the characteristic frequency for FB‐WIFF is more sensitive to fracture radius than that for elastic scattering. This is because the characteristic frequency for the FB‐WIFF is approximately inversely proportional to the square of the fracture radius (e.g., Galvin & Gurevich, ), whereas that for the elastic scattering is only inversely proportional to the fracture radius itself (Guo, Shuai, et al, ). Therefore, in the cases where the characteristic frequencies of FB‐WIFF and elastic scattering are not far away from each other, varying the fracture radius may result in significant strengthening of the coupling between FB‐WIFF and elastic scattering.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the scattering effect is strong when the ultrasonic wavelength is comparable to the fabric, pore, and/or microcrack sizes (Wu & Aki, 1988). Recent studies of coda waves at ultrasonic frequencies have been undertaken (e.g., Guo & Fu, 2007; Guo, Shuai, et al, 2018; Wei & Fu, 2014). Guo et al (2009) analyzed the pore pressure dependence of the coda and intrinsic attenuations by using the single scattering model in sandstones and observed that attenuation increases with pore pressure.…”
Section: Introductionmentioning
confidence: 99%